Proton exchange membrane and preparation method thereof
By using a proton exchange membrane containing hydroxy quaternary amine salt and N,N'-carbonyl diimidazole in all vanadium flow batteries, the penetration of vanadium ion is hindered by electrostatic repulsion, the problem of vanadium ion penetration at high temperature is solved, and the high level of vanadium ion penetration is achieved Improved efficiency and durability performance.
Patent Information
- Application Number
- CN202411661620.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In high temperature environments, vanadium ions are prone to permeate through the proton exchange membrane, resulting in a reduction in the Coulombic efficiency of all vanadium flow batteries, and the prior art is difficult to effectively prevent the penetration of vanadium ions.
The proton exchange membrane is prepared by blending quaternary amine salts containing hydroxyl groups, N,N'-carbonyldiimidazole and perfluorosulfonic acid resin solutions. The penetration of vanadium ions is hindered by electrostatic repulsion, and combined with N,N'-carbonyldiimidazole and The sulfonate links to form a vanadium-resisting effect.
Maintain high Coulomb efficiency and energy efficiency under high temperature conditions, and maintain the resistance and circulation capacity of the electrolyte under long-term high electrical tight conditions.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of proton exchange membranes, and in particular relates to a proton exchange membrane and a preparation method thereof. Background Art
[0002] Due to the influence of climate and geographical environment, renewable energy such as wind power, solar energy, and wind power are uncontrollable and discontinuous. Therefore, large-scale energy storage systems are needed to store these resources. Among several energy storage devices, all-vanadium redox flow battery (VRFB) has the advantages of independent adjustable energy and power capacity, fast response speed, and long life.
[0003] All-vanadium liquid flow batteries used in high-temperature environments can avoid the power loss caused by equipping them with additional cooling devices. The voltage performance of the battery can be greatly improved at high temperatures, and the viscosity of the electrolyte will decrease with the increase in temperature, the flow resistance will decrease, and the power consumption of the pump will also decrease. However, at higher temperatures, vanadium ions are easier to penetrate the membrane than at room temperature, resulting in a decrease in coulombic efficiency. Therefore, how to prevent vanadium ion penetration at high temperatures is currently a difficult problem in the research of proton exchange membranes. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a proton exchange membrane and a preparation method thereof. The proton exchange membrane prepared by the preparation method of the present invention is used in an all-vanadium liquid flow battery, which can enable the battery to maintain high coulombic efficiency and energy efficiency under high temperature conditions, as well as good electrolyte resistance and high cycle capacity retention rate under long-term high-current density conditions.
[0005] Specifically, the first aspect of the present invention provides a method for preparing a proton exchange membrane, characterized in that it comprises the following steps: (1) mixing a quaternary ammonium salt containing a hydroxyl group, N,N'-carbonyldiimidazole and a perfluorosulfonic acid resin solution to obtain a membrane-forming solution; (2) applying the film-forming solution on a substrate to obtain a wet film attached to the substrate; (3) Drying and annealing the substrate and the wet film thereon, and peeling off the formed membrane from the substrate to obtain the proton exchange membrane.
[0006] In one or more embodiments, the quaternary ammonium salt containing a hydroxyl group is obtained by quaternizing an amine compound containing a hydroxyl group, wherein the quaternizing agent is a halogenated alkane, for example, one or more selected from methyl iodide, methyl chloride, methyl bromide, ethyl chloride, ethyl bromide and butyl bromide.
[0007] In one or more embodiments, the hydroxyl-containing amine compound is selected from one or more of 2,4,6-tris(dimethylaminomethyl)phenol, bis[(dimethylamino)-methyl]phenol, 2-dimethylaminomethylphenol and {3-[(dimethylamino)methyl]phenyl}methanol.
[0008] In one or more embodiments, the molar ratio of the quaternary ammonium salt containing a hydroxyl group to N,N'-carbonyldiimidazole is 1:(0.8-1.2), such as 1:1.
[0009] In one or more embodiments, the mass ratio of the quaternary ammonium salt containing a hydroxyl group to the perfluorosulfonic acid resin is (0.01-0.08):1.
[0010] In one or more embodiments, in the perfluorosulfonic acid resin solution, the mass fraction of the perfluorosulfonic acid resin is 5wt%-30wt%, preferably 10wt%-20wt%.
[0011] In one or more embodiments, in the perfluorosulfonic acid resin solution, the solvent is N,N-dimethylformamide.
[0012] In one or more embodiments, the substrate layer is made of one or more of PEN, PI and PET.
[0013] In one or more embodiments, the coating is performed by solution casting.
[0014] In one or more embodiments, the coating gap is 300-500 μm.
[0015] In one or more embodiments, the coating speed is 8-12 mm / s.
[0016] In one or more embodiments, the drying method is oven drying, the drying temperature is 120-160° C., and the drying time is 8-12 min.
[0017] In one or more embodiments, the annealing process conditions are: the annealing temperature is 180-220° C., and the annealing time is 20-30 min.
[0018] In one or more embodiments, the proton exchange membrane has a thickness of 30-50 μm.
[0019] A second aspect of the present invention provides a proton exchange membrane prepared by the method for preparing a proton exchange membrane as described in any embodiment of the present invention.
[0020] The third aspect of the present invention provides a flow battery, which comprises a proton exchange membrane as described in any embodiment of the present invention. Preferably, the flow battery is an all-vanadium redox flow battery.
[0021] Beneficial effects of the present invention: The present invention selects quaternary ammonium salt containing hydroxyl group, N, N'-carbonyldiimidazole and perfluorosulfonic acid resin solution to be blended into the solution for preparing proton exchange membrane, uses N, N'-carbonyldiimidazole to link the solution with sulfonic acid radical, and the quaternary ammonium salt ions hinder the penetration of vanadium ions in the membrane through electrostatic repulsion, and the two cooperate with each other to achieve more obvious vanadium blocking effect; the prepared membrane is used in the all-vanadium liquid flow battery, so that the membrane can maintain high coulomb efficiency and energy efficiency under high temperature working conditions, and has good electrolyte resistance and high cycle capacity retention rate under long-term high-current density working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The discharge capacity curves of the proton exchange membranes of the embodiments and comparative examples after 100 charge and discharge cycles. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this article. Unless otherwise specified, all technical and scientific terms used in this article are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this article shall prevail.
[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0025] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0026] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0028] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a proton exchange membrane, the method comprising the following steps: (1) mixing a quaternary ammonium salt containing a hydroxyl group, N,N'-carbonyldiimidazole and a perfluorosulfonic acid resin solution to obtain a membrane-forming solution; (2) coating the film-forming liquid on the substrate to obtain a wet film attached to the substrate; (3) The substrate and the wet film thereon are dried and annealed, and the formed membrane is peeled off from the substrate to obtain a proton exchange membrane.
[0031] In some embodiments, the amine compound containing a hydroxyl group is subjected to a quaternary amination reaction with a quaternary amination agent to obtain a quaternary ammonium salt containing a hydroxyl group. The hydroxyl group may be an alcohol group and / or a phenol group. In some embodiments, the amine compound containing a hydroxyl group is a tertiary amine containing an alcohol group and / or a phenol group, for example, one or more selected from 2,4,6-tris(dimethylaminomethyl)phenol, di[(dimethylamino)-methyl]phenol, 2-dimethylaminomethylphenol and {3-[(dimethylamino)methyl]phenyl}methanol. The quaternary amination agent may be an alkylating agent. In some preferred embodiments, the alkylating agent is selected from halogenated alkanes, for example, one or more selected from methyl iodide, methyl chloride, methyl bromide, ethyl chloride, ethyl bromide and butyl bromide.
[0032] In some specific embodiments, a tertiary amine containing a phenol group and / or an alcohol group and a halogenated alkane are mixed and stirred under light-proof conditions to synthesize a quaternary ammonium salt. The stirring speed may be 250-350 rpm. The stirring time may be 24-48 hours.
[0033] The present invention finds that by selecting a quaternary ammonium salt containing a hydroxyl group and blending it into a proton exchange membrane solution to make a membrane to achieve the effect of vanadium blocking, the all-vanadium liquid flow battery can maintain high coulombic efficiency and energy efficiency under high temperature conditions, and has good electrolyte resistance and high cycle capacity retention rate under long-term high-current density conditions.
[0034] In some embodiments, the molar ratio of the quaternary ammonium salt containing a hydroxyl group to N, N'-carbonyldiimidazole is 1: (0.8-1.2) such as 1: 1. The present invention finds that by selecting N, N'-carbonyldiimidazole as a cross-linking agent and linking it with a sulfonic acid group, the vanadium barrier effect of the obtained membrane is more obvious, so that the all-vanadium liquid flow battery can maintain high coulombic efficiency and energy efficiency under high temperature conditions, and has good electrolyte resistance and high cycle capacity retention rate under long-term high-density conditions.
[0035] In some embodiments, the mass ratio of the quaternary ammonium salt containing a hydroxyl group to the perfluorosulfonic acid resin solution is (0.01-0.08):1.
[0036] In the perfluorosulfonic acid resin solution of the present invention, the mass fraction of the perfluorosulfonic acid resin may be 5wt%-30wt%, preferably 10wt%-20wt%. In some embodiments, the solvent in the perfluorosulfonic acid resin solution is N,N-dimethylformamide.
[0037] In some embodiments, the perfluorosulfonic acid resin is dissolved in a solvent such as N,N-dimethylformamide to form a perfluorosulfonic acid resin solution. In some specific embodiments, the perfluorosulfonic acid resin is dissolved in N,N-dimethylformamide and stirred until completely dissolved. The dissolving temperature may be 20-80°C or 60°C-80°C. An exemplary stirring time may be 3-5h.
[0038] In some embodiments, the perfluorosulfonic acid resin dispersion is evaporated to obtain a dried perfluorosulfonic acid resin. Commercially available perfluorosulfonic acid resin dispersions, such as Nafion D520 dispersions and Nafion D2020 dispersions, can be used. The temperature and time for evaporating the perfluorosulfonic acid resin dispersion can be determined according to the properties of the resin dispersion itself, such as the type of solvent, to obtain the perfluorosulfonic acid resin. The evaporation temperature can be 60-120° C. or 70-90° C. The evaporation time can be 8-12 hours.
[0039] In some embodiments, in step (1), a perfluorosulfonic acid resin solution, a quaternary ammonium salt containing a hydroxyl group and N,N'-carbonyldiimidazole can be mixed and then dispersed to obtain a film-making solution. The dispersion method can be to use a homogenizer for dispersion. There is no particular limitation on the time and speed of dispersion, as long as the dispersion is uniform. An exemplary dispersion time can be 10min-30min, and the dispersion speed can be 10000-20000 rpm. The mass ratio of the quaternary ammonium salt containing a hydroxyl group to the perfluorosulfonic acid resin can be (0.01-0.08):1, such as 0.01-0.05 or 0.05-0.08. The mass of the perfluorosulfonic acid resin refers to the mass of the solute perfluorosulfonic acid resin in the perfluorosulfonic acid resin solution.
[0040] In some embodiments, in step (2), the film-making liquid can be poured onto the substrate and coated by a casting coater. The coating gap can be 350-450 μm, such as 400-420 μm. The coating speed can be 8-15 mm / s, such as 9-12 mm / s. The coating thickness of the film-making liquid on the substrate surface can be adjusted according to the target thickness of the film. The material of the substrate layer can be one or more of PEN (polyethylene naphthalate), PI (polyimide) and PET (polyethylene terephthalate).
[0041] In some embodiments, in step (3), the obtained wet film can be placed in an oven such as a forced air oven for drying to evaporate the solvent. The drying temperature can be 120-160° C., such as 135-145° C. The drying time can be 8-12 min.
[0042] After drying, a dry film is obtained, and then annealing is performed. In some embodiments, the dry film can be placed in an oven such as a forced air oven for annealing. The annealing conditions can be an annealing temperature of 180-220° C. and an annealing time of 20-30 min. The membrane is peeled off from the substrate to obtain the final proton exchange membrane.
[0043] The present invention also includes an all-vanadium redox flow battery, which comprises a positive electrode, a negative electrode, a proton exchange membrane of the present invention and an electrolyte. The positive and negative electrodes of the battery are separated by the proton exchange membrane of the present invention.
[0044] In the present invention, the structure of the all-vanadium redox flow battery, the positive and negative electrolytes, and the method for making the all-vanadium redox flow battery are conventional in the art.
[0045] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0046] The Nafion D520 resin dispersion used in the examples and comparative examples was purchased from Thermo Fisher Scientific.
[0047] Example 1
[0048] Step 1: Pour the purchased Nafion D520 dispersion into an evaporating dish, adjust the oven to 80°C, and place the evaporating dish in the oven for 10 hours to obtain Nafion resin. Add 20g of the obtained Nafion resin and 80g of DMF solvent into a reactor, stir at 80°C for 4 hours, and set the stirring speed to 300 rpm. Stop stirring after observing that the Nafion resin is completely dissolved, and obtain a perfluorosulfonic acid resin solution with a mass fraction of 20wt%.
[0049] Step 2: Weigh 100 g of 2,4,6-tris(dimethylaminomethyl)phenol and 53.48 g of iodomethane on an analytical balance in the dark, mix 2,4,6-tris(dimethylaminomethyl)phenol and iodomethane, stir with a magnetic stirrer at 300 rpm for 24 hours to obtain a quaternary ammonium salt of 2,4,6-tris(dimethylaminomethyl)phenol.
[0050] Step 3: 100 g of the perfluorosulfonic acid resin solution obtained in step 1, 1 g of the quaternary ammonium salt obtained in step 2, and 0.611 g of N,N'-carbonyldiimidazole were weighed and mixed together, and dispersed evenly using a homogenizer for 20 min at a stirring speed of 10,000 rpm to obtain a membrane-making solution.
[0051] Step 4: Pour the film-making solution obtained in step 3 onto the polyimide substrate, and coat the film with a gap of 400 μm, a running speed of 10 mm / s, and a distance of 400 mm through a casting coater to obtain a wet film.
[0052] Step 5: The obtained wet film was baked in an oven at 140°C for 10 minutes to remove the solvent.
[0053] Step 6: The dry membrane was placed in an oven at 200° C. for 25 minutes for annealing to obtain a proton exchange membrane with a thickness of 40 μm.
[0054] Example 2
[0055] The difference from Example 1 is that the amount of the quaternary ammonium salt of 2,4,6-tris(dimethylaminomethyl)phenol is reduced to 0.2 g, and the amount of N,N'-carbonyldiimidazole is reduced to 0.122 g. The remaining operating conditions and steps are the same as those in Example 1.
[0056] Example 3
[0057] The difference from Example 1 is that the amount of the quaternary ammonium salt of 2,4,6-tris(dimethylaminomethyl)phenol is increased to 1.6 g, and the amount of N,N'-carbonyldiimidazole is increased to 0.978 g. The remaining operating conditions and steps are the same as those in Example 1.
[0058] Example 4
[0059] The difference from Example 1 is that the quaternization reaction raw materials are replaced with 100 g of di[(dimethylamino)-methyl]phenol and 24.2 g of methyl chloride. The remaining operating conditions and steps are the same as those in Example 1.
[0060] Comparative Example 1
[0061] Step 1: Use the perfluorosulfonic acid resin solution obtained in step 1 of Example 1 to coat the polyimide substrate, set the gap of the casting coater to 400 μm, set the running speed to 10 mm / s, set the distance to 400 mm, and coat to obtain a wet film.
[0062] Step 2: The obtained wet film was baked in an oven at 140° C. for 10 minutes to remove the solvent and obtain a dry film.
[0063] Step 3: The dry membrane was placed in an oven at 200° C. for 25 minutes for annealing to obtain a proton exchange membrane with a thickness of 40 μm.
[0064] Comparative Example 2
[0065] The difference from Example 1 is that 2,4,6-tris(dimethylaminomethyl)phenol is not quaternized, but is directly blended with N,N'-carbonyldiimidazole and perfluorosulfonic acid resin solution to form a dry film.
[0066] Comparative Example 3
[0067] The difference from Example 1 is that the perfluorosulfonic acid resin solution is only blended with the quaternary ammonium salt obtained in step 2, and N,N'-carbonyldiimidazole is not added.
[0068] Comparative Example 4
[0069] The difference from Example 1 is that the perfluorosulfonic acid resin solution is only blended with N,N'-carbonyldiimidazole, and no quaternary ammonium salt is added.
[0070] Comparative Example 5
[0071] The difference from Example 1 is that N,N'-carbonyldiimidazole is replaced by an equal mole of 4-dimethylaminopyridine. The remaining operating conditions and steps are the same as those in Example 1.
[0072] Test Example 1
[0073] The performance of the all-vanadium redox flow battery prepared by using the proton exchange membrane for all-vanadium redox flow battery of Examples 1-4 and Comparative Examples 1-5 was tested. The test conditions were as follows: at a current density of 80 mA / cm 2 -240mA / cm 2 The charge and discharge experiments were carried out under the following conditions: charging to 1.55V and discharging to 1.00V, and the effective working area of the electrode was 48cm 2 The positive and negative electrolytes are VO 2+ / VO2 + and V 2+ / V 3+ of sulfuric acid solution, the battery operating temperature is 45°C.
[0074] The coulombic efficiency and energy efficiency results of the all-vanadium redox flow batteries prepared using the proton exchange membranes of Examples 1-4 and Comparative Examples 1-5 are shown in Table 1. CE represents coulombic efficiency and EE represents energy efficiency.
[0075] Table 1: Performance test of proton exchange membrane vanadium flow battery at different current densities
[0076] As can be seen from Table 1, the vanadium crossover of the flow battery under high temperature conditions in Comparative Examples 1-5 is serious, and the coulombic efficiency is low. In Example 1-4, a quaternary ammonium salt containing a hydroxyl group and N,N'-carbonyldiimidazole are simultaneously introduced in the preparation of the proton exchange membrane solution, so that the ion membrane contains positively charged cationic groups, which makes it difficult for vanadium ions to pass through the ion membrane, thereby increasing the coulombic efficiency of the flow battery. Due to the increase in coulombic efficiency, the overall energy efficiency of the battery will also increase.
[0077] Test Example 2
[0078] The long-term durability of the all-vanadium redox flow battery prepared using the proton exchange membranes of Example 1 and Comparative Examples 1-5 was tested. The test conditions were as follows: at a current density of 240 mA / cm 2 The charge and discharge experiments were carried out under the following conditions: charging to 1.55V and discharging to 1.00V, and the effective working area of the electrode was 48cm 2 The positive and negative electrolytes are VO 2+ / VO2 + and V 2+ / V 3+ sulfuric acid solution, the battery operating temperature is 45°C, and the charge and discharge are 100 cycles.
[0079] Figure 1 At a current density of 240 mA / cm 2 The discharge capacity curves of the proton exchange membranes of Example 1 and Comparative Examples 1-5 after 100 cycles of charge and discharge under the conditions shown in FIG. It can be seen from the figure that under long-term high-density conditions, the proton exchange membrane of Example 1 blended with quaternary ammonium salt ions and N,N'-carbonyldiimidazole has no problem with electrolyte resistance under long-term durability tests, and the capacity is better than that of Comparative Examples 1-5.
[0080] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a proton exchange membrane, characterized in that: It includes the following steps: (1) mixing a quaternary ammonium salt containing a hydroxyl group, N,N'-carbonyldiimidazole and a perfluorosulfonic acid resin solution to obtain a membrane-forming solution; (2) applying the film-forming solution on a substrate to obtain a wet film attached to the substrate; (3) Drying and annealing the substrate and the wet film thereon, and peeling off the formed membrane from the substrate to obtain the proton exchange membrane.
2. The method according to claim 1, characterized in that The quaternary ammonium salt containing a hydroxyl group is obtained by a quaternary amination reaction of an amine compound containing a hydroxyl group, wherein the quaternary amination agent is a halogenated alkane, for example, one or more selected from methyl iodide, methyl chloride, methyl bromide, ethyl chloride, ethyl bromide and butyl bromide, and the amine compound containing a hydroxyl group is one or more selected from 2,4,6-tris(dimethylaminomethyl)phenol, di[(dimethylamino)-methyl]phenol, 2-dimethylaminomethylphenol and {3-[(dimethylamino)methyl]phenyl}methanol.
3. The method according to claim 1, characterized in that The molar ratio of the quaternary ammonium salt containing hydroxyl group to N,N'-carbonyldiimidazole is 1:(0.8-1.2).
4. The method according to claim 1, characterized in that The mass ratio of the quaternary ammonium salt containing hydroxyl group to the perfluorosulfonic acid resin is (0.01-0.08):
1.
5. The method according to claim 1, wherein In the perfluorosulfonic acid resin solution, the mass fraction of the perfluorosulfonic acid resin is 5wt%-30wt%; and / or In the perfluorosulfonic acid resin solution, the solvent is N,N-dimethylformamide.
6. The method according to claim 1, characterized in that The method has one or more of the following features: The material of the substrate layer is one or more of PEN, PI and PET; The coating method is solution casting coating; The coating gap is 300-500 μm; The coating speed is 8-12 mm / s.
7. The method according to claim 1, characterized in that The drying method is drying at a temperature of 120-160° C. and a drying time of 8-12 minutes; and / or The annealing process conditions are as follows: the annealing temperature is 180-220° C., and the annealing time is 20-30 min.
8. The method according to claim 1, characterized in that The thickness of the proton exchange membrane is 30-50 μm.
9. A proton exchange membrane prepared by the method according to any one of claims 1 to 8.
10. A liquid flow battery, characterized in that: It comprises the proton exchange membrane as claimed in claim 9.
Citation Information
Patent Citations
Cross-linking perfluorinated sulfonic acid ion exchange membrane and preparation method thereof
CN101764233A
Sulfonated polyether ether ketone capable of being used as crosslinking proton exchange membrane material and purpose thereof
CN106117473A
Amphoteric ion exchange resin solution, flow battery diaphragm and all-vanadium flow battery
CN117487201A
Preparation method of quaternized polypiperazine / perfluorosulfonic acid resin zwitter-ion blended membrane
CN118515898A
